Criminal Disparity in Judges' Decisions on The Crime of Sexual Intercourse Against Minors - Himawan, Yuniar Yudha; Muhibbin, Moh; Parmono, Budi (JURNAL USM LAW REVIEW, 2025)
The purpose of this research is to compare judges' decisions that give different sentences for the same criminal offense. Judges' decisions often provide different sentences for the same criminal offense because the positive criminal system in Indonesia uses an alternative system. This research raises the issue of why there is criminal disparity in the Supreme Court's decision related to the crime of sexual intercourse with a minor and how to reduce criminal disparity related to this crime. The urgency of this research is to find out and explain the imposition of criminal law, compare judges' decisions on the imposition of criminal law, and the impact of criminal disparity in cases of child sexual intercourse which has a serious impact on public confidence in the criminal justice system and the protection of children as a vulnerable group. This research is a normative juridical research using primary and secondary materials. The result of the research shows that: 1) There is a criminal disparity between Supreme Court Decision No. 2184K/Pid.Sus/2022 where the defendant was sentenced to 5 years imprisonment and a fine of Rp. 30,000,000.00 with Supreme Court Decision No. 2199K/Pid.Sus/2022 where the defendant was sentenced to 2 years imprisonment and a fine of Rp. 20,000,000.00. 2) The cause of criminal disparity is a legal factor that does not contain guidelines for the imposition of punishment for the defendant.